2022
DOI: 10.1029/2021gb007038
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Responses of Soil Inorganic Carbon to Afforestation in Acidic Versus Alkaline Soils

Abstract: Globally about 950 petagrams (Pg) carbon is stored in soils in inorganic form (Schlesinger, 1990;Schlesinger & Andrews, 2000). The size of this global soil inorganic carbon (SIC) pool is smaller than that of soil organic carbon (SOC, 1,550 Pg, Lal, 2004) but more than that of vegetation carbon (450-650 Pg, Friedlingstein et al., 2020). This large SIC pool is usually considered stable and thus has received little attention, especially when compared with SOC (Zamanian et al., 2018). However, SIC can regulate glo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…As expected, our analyses also support the importance of abiotic factors (e.g., soil properties) in explaining the global variation in topsoil SIC. Our results aligned with numerous studies that emphasized the crucial roles of lithology (i.e., carbonate rocks), soil pH, texture, bulk density, Ca, and EC in explaining the distribution of SIC (Ferdush & Paul, 2021; Hong & Chen, 2022; Tao et al., 2022). However, it is unexpected that despite the positive correlation between soil pH and SIC (Figure S6 in Supporting Information S1), soil pH had a potentially negative effect on SIC when we considered other environmental factors (Figures 2b and 4b).…”
Section: Discussionsupporting
confidence: 91%
“…As expected, our analyses also support the importance of abiotic factors (e.g., soil properties) in explaining the global variation in topsoil SIC. Our results aligned with numerous studies that emphasized the crucial roles of lithology (i.e., carbonate rocks), soil pH, texture, bulk density, Ca, and EC in explaining the distribution of SIC (Ferdush & Paul, 2021; Hong & Chen, 2022; Tao et al., 2022). However, it is unexpected that despite the positive correlation between soil pH and SIC (Figure S6 in Supporting Information S1), soil pH had a potentially negative effect on SIC when we considered other environmental factors (Figures 2b and 4b).…”
Section: Discussionsupporting
confidence: 91%
“…Our work also provided a typical example of how fine‐scale microbial activities were upscaled to shape ecosystem functional processes under long‐term afforestation. Importantly, recent studies indicated that soil physical structure varied significantly and was important factor driving soil C stocks under large‐scale afforestation (e.g., at the regional and global‐scale) (Hong & Chen, 2022; Nave et al., 2021). Therefore, further studies are needed to better understand the role of fine‐scale soil microbial P acquisition in driving soil C sequestration under afforestation at large‐scale, in order to better predict soil P dynamics and its impacts on C sequestration following future afforestation.…”
Section: Discussionmentioning
confidence: 99%
“…In less arid regions, however, vegetation cover's effect on total carbon is negative. Increased vegetation cover may enhance organic carbon decomposition (Shahzad et al, 2015) and result in a decrease in inorganic carbon (Hong & Chen, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In less arid regions, however, vegetation cover's effect on total carbon is negative. Increased vegetation cover may enhance organic carbon decomposition (Shahzad et al., 2015) and result in a decrease in inorganic carbon (Hong & Chen, 2022). At low aridity levels, biocrusts prevent organic carbon from being eroded (Chamizo et al., 2017), whereas at high aridity levels, crusts can produce organic acids (Belnap, 2011) that can lead to inorganic carbon decomposition.…”
Section: Discussionmentioning
confidence: 99%